2012
DOI: 10.1177/1933719111433886
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of PARD3 Gene Polymorphisms With Neural Tube Defects in a Chinese Han Population

Abstract: Partitioning defective 3 homolog (PARD3) is an attractive candidate gene for screening neural tube defect (NTD) risk. To investigate the role of genetic variants in PARD3 on NTD risk, a case-control study was performed in a region of China with a high prevalence of NTDs. Total 53 single-nucleotide polymorphisms (SNPs) in PARD3 were genotyped in 224 fetuses with NTDs and in 253 normal fetuses. We found that 6 SNPs (rs2496720, rs2252655, rs3851068, rs118153230, rs10827337, and rs12218196) were statistically asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Previous studies supported that low folate levels, and polymorphism of folate-metabolic genes were risk factors for NTDs in this region [58], [59], [60]. Genes regulating early embryonic development were also identified as risk factors of NTDs in this region [61], [62], [63]. The significant involvement of copy number variants in NTD revealed by this study further suggests the complex genetic heterogeneity underlying NTD pathogenesis in the Shanxi region.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies supported that low folate levels, and polymorphism of folate-metabolic genes were risk factors for NTDs in this region [58], [59], [60]. Genes regulating early embryonic development were also identified as risk factors of NTDs in this region [61], [62], [63]. The significant involvement of copy number variants in NTD revealed by this study further suggests the complex genetic heterogeneity underlying NTD pathogenesis in the Shanxi region.…”
Section: Discussionsupporting
confidence: 77%
“…Previous genotyping of 53 tag PARD3 SNPs had confirmed that subjects in this cohort represent the same Chinese ethnic group [Gao, et al., ]. After removing any questionable sequencing data and common variants, a total of 60 rare PARD3 variants including synonymous, missense, and splicing variants remained for comparison (Supp.…”
Section: Resultsmentioning
confidence: 87%
“…In humans, PARD3 (MIM# 606745) intragenic microdeletions and missense mutations have been identified at high frequency in human epithelial cancer cell lines [Rothenberg, et al., ]. We previously reported a significant association between common SNPs of PARD3 (rs2496720, rs2252655, rs3851068, and rs118153230) and NTDs, and this association was more significant for cranial rather than spinal defects [Gao, et al., ]. Given the importance of PARD3 in neuroepithelial morphology, we hypothesized that rare PARD3 genomic variants are risk factors for human cranial NTDs.…”
Section: Introductionmentioning
confidence: 99%
“…In the vertebrate embryo, there are two types of neuroepithelial cell division, i.e., apicobasal and planar cell divisions [23]. The development of cell polarity plays a crucial role in the process of neurulation, being implied in the neural tube closure [23]. Neurulation represents the process of neural tube formation during early embryogenesis.…”
Section: R J M Ementioning
confidence: 99%